Analisis Pendekatan Malcolm Baldrige Terhadap Kinerja Rumah Sakit Umum Daerah Kota Batam - Heryenzus Heryenzus; Suali Suali (LPPM Universitas Putera Batam, 2018)
To measure and improve hospital performance, Malcolm Baldrige is present for maximum achievement in Total Quality Management. This study aims to measure the achievement of Batam Regional General Hospital by using MBCfPE for business criteria and to know and analyze the influence of MBCfPE on hospital performance. This research is an observational descriptive research with cross-sectional research design applied. Total sample of 200 employees by using simple random sampling. The results of the survey through MBCfPE showed that the overall total score of the performance assessment achieved by this hospital was 763 and the results indicated that the hospital's performance was Business Leader. Based on the criteria of Malcolm Baldrige, the performance of Batam City Hospital is seen from the criteria of leadership; strategic planning criteria; measurement, analysis, and knowledge management criteria; human resource focus criteria; as well as the criteria of the focus of operational activities, the performance of Batam city hospitals included in the good category. The performance of Batam city hospitals based on Malcolm Baldrige points points included in very good performance category (763,93). And on the performance achievement of each criterion, if the result point value obtained compared to the maximum points value in Malcolm Baldrige, the leadership criteria achieved the highest performance performance with the percentage of 75.93%. The lowest performance achievement is owned by human resource focus criteria of 64.42%. It can be concluded that the performance of RSUD Kota Batam criteria Malcolm Baldrige very good.